2014
DOI: 10.11138/per/2014.3.2.060
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgical treatment of rectovaginal fistula: an original technique

Abstract: SummaryBackground: rectovaginal fistulas (RVFs) are a rare surgical condition. Their treatment is extremely difficult, and no standard surgical technique is accepted worldwide. This report describes a new approach using transanal endoscopic microsurgery (TEM) to treat RVFs. Materials and Methods: a retrospective review of 13 patients who underwent repair of rectovaginal fistula using TEM between 2001 and 2008 was undertaken. The surgical technique is widely described, and the advantages of the endorectal appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Management of RUF is especially difficult because of the high frequency of comorbidities and risk factors for poor wound healing such as history of cancer and radiation therapy. Rectourethral fistula repair has been reported with varying degree of success (62%–100%) with wide-ranging patient populations, follow-up length, and surgical approaches 8,14–16 . Our single-center retrospective study demonstrated a 92% success rate of RUF repair with gracilis flap, which falls in the higher end of the range of previously reported studies, including a meta-analysis of 416 patients who had surgical repair for RUF with an overall success rate of 87.5% 1 …”
Section: Discussionmentioning
confidence: 58%
“…Management of RUF is especially difficult because of the high frequency of comorbidities and risk factors for poor wound healing such as history of cancer and radiation therapy. Rectourethral fistula repair has been reported with varying degree of success (62%–100%) with wide-ranging patient populations, follow-up length, and surgical approaches 8,14–16 . Our single-center retrospective study demonstrated a 92% success rate of RUF repair with gracilis flap, which falls in the higher end of the range of previously reported studies, including a meta-analysis of 416 patients who had surgical repair for RUF with an overall success rate of 87.5% 1 …”
Section: Discussionmentioning
confidence: 58%